(untitled) (Economic studies journal, 2021)
Abstract This study aimed to identify the reality of the application of knowledge management, the reality and reality of a process, as well as to know the effect of knowledge management separately (represented in knowledge Acquisition, knowledge storage, knowledge sharing, knowledge mark, knowledge mark), and to determine the Cumulative effect of the combined dimensions of management in a process. Innovation in the trade and development Zone in the city of Benghazi, and to achieve the objectives of the study, the researcher followed the descriptive and Analytical approach and the data for the study were collected by means of a questionnaire form from the study Population consisting of (95) employees holding the position of director, deputy director, and head of a department In the study bank, and following the survey method Comprehensive for all society and data data and mathematics Through the Statistical program (spas). The results of the study revealed that the level of knowledge management Implementation and the level of innovation process in the bank under study are considered high, and that there is a Statistically significant effect for each dimension of knowledge management on the innovation process, as well as a Cumulative effect of statistical significance for the combined dimensions of knowledge management on the process. Innovation, and thus we reject the null hypotheses and accept the alternative hypotheses in this study.